THE INTERCONNECTION BETWEEN MICROBIOTA AND STRESS HORMONES IN THE HUMAN BODY: A NEW SCIENTIFIC APPROACH - Qahramonov Davron Dilshod o‘g‘li (World Scientific Research Journal, 2025)
This article analyzes the mechanisms of interaction between the microbiota and stress hormones, particularly cortisol, in the human body. The microbiota plays a vital role in ensuring internal environmental stability and mental health. The study explores the mechanisms of the microbiota’s involvement in physiological responses to stress, as well as the neuroendocrine communication within the microbiota-gut-brain axis. Analyses have shown that increased stress levels can disrupt various components of the microbiota, thereby negatively impacting health. New scientific approaches and metagenomic tools are expanding opportunities to study the role of the microbiota in health more deeply.